Behind the Vow: Factors and Portrayals of Failed Marriage in The Seven Husbands of Evelyn Hugo - Wini Amartiya Balqis; Desri Maria Sumbayak; Dian Marisha Putri (Talenta Publisher, 2026)
Understanding literature is not as simple as it appears. Each person has their own interpretation of the literary works themselves. The research aims to analyse failed marriages portrayed in Taylor Jenkins Reid's ‘The Seven Husbands of Evelyn Hugo’ and find out what are the factors of the failed marriage in the novel, how the failed marriage is portrayed in the novel and how the characters deal with the failed marriage in the novel. The researcher used descriptive qualitative research, and the data were formed by words and sentences from The Seven Husbands of Evelyn Hugo novel. The research revealed that the factors of failed marriage are career development, infidelity, expectation gap, and selfishness. Meanwhile, the failed marriage is portrayed using a first-person point of view with two narrators switching back and forth; also, the characters deal with the failed marriage by having a conflict with him/herself, the environment, and another person. The Seven Husbands of Evelyn Hugo depicts Evelyn’s struggle to conceal her true self while striving to become a celebrity and shape the public’s perception of her. To love forward in her career, Evelyn develops increasingly complicated lies and deceptions throughout her marriages.